Mediators of the Effect of Corneal Cross-Linking on Visual Acuity for Fungal Ulcers: A Prespecified Secondary Analysis From the Cross-Linking–Assisted Infection Reduction Trial. Issue 10 (17th October 2022) - Prajna, N. Venkatesh; Radhakrishnan, Naveen; Lalitha, Prajna; Liu, Zijun; Keenan, Jeremy D.; Arnold, Benjamin F; Rose-Nussbaumer, Jennifer
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to determine whether astigmatism or corneal scarring is mediating the reduced visual acuity among patients with fungal keratitis randomized to corneal cross-linking (CXL). Design: This was a prespecified exploratory outcome from an outcome-masked, 2 × 2 factorial design, randomized controlled clinical trial. Study Participants: Consecutive patients presented with moderate vision loss from a smear-positive fungal ulcer at Aravind Eye Hospital, Madurai, India. Intervention: Study eyes were randomized to one of 4 treatment combinations using an adaptive randomization protocol. The treatment arms included (1) topical natamycin 5% alone, (2) topical natamycin 5% plus CXL, (3) topical amphotericin B 0.15% alone, and (4) topical amphotericin 0.15% plus CXL. Best spectacle-corrected visual acuity (BSCVA), contact lens over-refraction, and scar size and depth as measured by a masked study ophthalmologist using a standardized protocol were recorded at 3 months. Pentacam Scheimpflug imaging was also obtained at 3 months. Main Outcome Measures: BSCVA and contact lens over-refraction, infiltrate and/or scar size and depth, total astigmatism of the front and back of the cornea, total lower-order and higher-order aberrations of the anterior and posterior cornea, and total densitometry of the anterior, central, and posterior stroma were recorded. We performed a mediation analysis looking at the proportion of the effect of CXL on BSCVA that was mediated through scar size, scar depth, astigmatism and density. Results: BSCVA at 3 months was available for 99 of 111 patients (89%) who had a mean of 0.82-LogMAR (SD 0.68). Three-month infiltrate and/or scar size ( P < 0.001), depth ( P < 0.001), and densitometry ( P = 0.001) were statistically significant predictors of 3-month BSCVA. Astigmatism seemed to mediate 23% of the effect of CXL on BSCVA, whereas scar size mediated 23%, scar depth 17%, and densitometry 7%. Conclusions: Corneal scarring and astigmatism are mediators of worse visual acuity after cross-linking in fungal keratitis. Corneal densitometry may be a helpful cornea-specific variable for clinicians and researchers in determining the effect of corneal scarring on visual acuity in specific patients and as an objective study outcome. Trial Registration: NCT02570321.